2018
DOI: 10.1007/s10816-018-9372-4
|View full text |Cite
|
Sign up to set email alerts
|

Birch Bark Tar Production: Experimental and Biomolecular Approaches to the Study of a Common and Widely Used Prehistoric Adhesive

Abstract: Birch bark tar, the oldest adhesive known in Europe, was widely used during Prehistory. This material, produced by the dry distillation of birch bark, has been identified in various spheres of activities and provides valuable information on the know-how and technical and territorial systems of past societies. This biomaterial can also provide evidence on socio-economic networks and mobility. However, very little is known about the production systems of birch bark tar during Prehistory, including the Neolithic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 47 publications
(66 reference statements)
3
66
0
Order By: Relevance
“…This has been the case of the 2 oldest GC-MS-analyzed examples of birch tar from Campitello and Königsaue (24,25). Analyzing our own experimental tar, we also identified both biomarkers (betulin and lupeol) in addition to 3 degraded markers (lupa-2,20 [29]-diene, α-betuline I, and lupa-2,20 [29]-dien-28-ol) that have been described to indicate heat treatment in previous experimental studies (22) and that were found in archaeological tar samples (26). Thus, tar produced in oxygenized environments with our experimental setup provides a molecular signature of birch bark tar.…”
Section: Significancementioning
confidence: 53%
See 1 more Smart Citation
“…This has been the case of the 2 oldest GC-MS-analyzed examples of birch tar from Campitello and Königsaue (24,25). Analyzing our own experimental tar, we also identified both biomarkers (betulin and lupeol) in addition to 3 degraded markers (lupa-2,20 [29]-diene, α-betuline I, and lupa-2,20 [29]-dien-28-ol) that have been described to indicate heat treatment in previous experimental studies (22) and that were found in archaeological tar samples (26). Thus, tar produced in oxygenized environments with our experimental setup provides a molecular signature of birch bark tar.…”
Section: Significancementioning
confidence: 53%
“…2D). Sample extraction and analytical conditions were performed following protocols established for birch tar analysis (22). GC-MS has previously been used to identify Paleolithic tar as being birch bark tar through the presence of characteristic pentacyclic triterpenes, in particular, betulin and lupeol (23), and their degradation markers that may indicate heat treatment (e.g., lupa-2,20 [29] diene, lupa-2,20 [29]-dien-28-ol, and allobetul-2-en).…”
Section: Significancementioning
confidence: 99%
“…These categories of molecular biomarkers were recently defined by a programme of experimental archaeology by Rageot et al . (2019). Some of them, such as lupa-2,20(29)-dien, lupa-2,20(29)-dien-28-ol and betulone, may also result from natural decay.…”
Section: Materials Identified In the Analysed Samplesmentioning
confidence: 99%
“…; Rageot et al . ). Other substances identified through residue analysis are more ambiguous to interpret, and so far there has been little consideration about whether fats, oils and waxes used in the manufacture of pottery leave a significant residue signal following firing.…”
Section: Introductionmentioning
confidence: 97%
“…The study of lipid residues in archaeological pottery has advanced significantly over the past decade and it has yielded new information about the prehistoric diet and cuisine (Craig et al 2013;Lucquin et al 2016b;Gibbs et al 2017). Various lipid compounds, such as tars, resins and waxes, have also been identified which were clearly used to repair pottery and to waterproof porous vessels, and had nothing to do with food preparation or cuisine (Regert et al 2003;Regert 2004;Hjulström et al 2006;Reber and Hart 2008;Stern et al 2008;Rageot et al 2019). Other substances identified through residue analysis are more ambiguous to interpret, and so far there has been little consideration about whether fats, oils and waxes used in the manufacture of pottery leave a significant residue signal following firing.…”
Section: Introductionmentioning
confidence: 99%